AN ANALYSIS OF TABOO WORDS IN WILD CHILD MOVIE. - HIDAYAH NOR; MAS DARUL IHSAN (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2017)
The author explores the form of taboo words used by the characters in Wild Child movie and the differences taboo words used between British and American in movie. The movie tells about a young rich girl’s life who has name is Poppy Moore. She is an American and has a best life, but there is a problem with her fellowship. It causes her mother was gone when she was child. She always gets everything what she wants and doing anything. Her father and little sister are very sad about her habits and attitudes, so that her father decide to send her to Abbey Mount School, England. This study used descriptive qualitative as the method for describing the current condition in movie. The data were in the form of utterances, and the contexts of the data were the dialogues uttered by the characters in movie. The sources of the data were the video movie of Wild Child movie and its transcript. The data were collected by selecting dialogues containing taboo words after watching the movie and matching the transcript with the video. The first instrument of this study was the author, and the second instrument was a data sheet.The results of this study are stated as follows. First, the form of taboo words occur in the characters’ utterances in Wild Child movie. Second, the the differences taboo words used between British and American in this movie.